2017
DOI: 10.1111/pce.13016
|View full text |Cite
|
Sign up to set email alerts
|

Airborne signals from Trichoderma fungi stimulate iron uptake responses in roots resulting in priming of jasmonic acid‐dependent defences in shoots of Arabidopsis thaliana and Solanum lycopersicum

Abstract: Root colonization by Trichoderma fungi can trigger induced systemic resistance (ISR). In Arabidopsis, Trichoderma-ISR relies on the transcription factor MYB72, which plays a dual role in the onset of ISR and the activation of Fe uptake responses. Volatile compounds (VCs) from rhizobacteria are important elicitors of MYB72 in Arabidopsis roots. Here, we investigated the mode of action of VCs from Trichoderma fungi in the onset of ISR and Fe uptake responses. VCs from Trichoderma asperellum and Trichoderma harzi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(105 citation statements)
references
References 89 publications
3
96
0
6
Order By: Relevance
“…However, when multiple volatile signals have to be integrated, the immune (or defence) response can also be reduced. Hormonal cross‐talk has a role in balancing trade‐offs, which can also result in the suppression of volatile emission (Martínez‐Medina et al ., ; Erb, ). Therefore, plants can produce specific volatiles upon microbial interactions but, in turn, microbes have been shown to be able to suppress VOC biosynthesis through the use of effectors (Sharifi et al ., ).…”
Section: The Role Of Vocs In the Interaction Of Plants With Micro‐orgmentioning
confidence: 99%
“…However, when multiple volatile signals have to be integrated, the immune (or defence) response can also be reduced. Hormonal cross‐talk has a role in balancing trade‐offs, which can also result in the suppression of volatile emission (Martínez‐Medina et al ., ; Erb, ). Therefore, plants can produce specific volatiles upon microbial interactions but, in turn, microbes have been shown to be able to suppress VOC biosynthesis through the use of effectors (Sharifi et al ., ).…”
Section: The Role Of Vocs In the Interaction Of Plants With Micro‐orgmentioning
confidence: 99%
“…Besides promoting plant growth, WCS417 is also a potent elicitor of ISR. Recently, it was demonstrated that the onset of ISR in Arabidopsis and tomato coincides with the activation of the iron deficiency response in colonized roots Martinez-Medina et al, 2017). The onset of both ISR and the iron deficiency response by ISR-inducing rhizobacteria is marked by the activation of the root-specific transcription factor gene MYB72 and the high-affinity iron transporter gene IRON-REGULATED TRANSPORTER1 (IRT1; Van der Ent et al, 2008;Zamioudis et al, 2015).…”
Section: Auxin Signature In Early Root Response To Wcs417mentioning
confidence: 99%
“…Root border cells and root exudates play a crucial role in shaping the microbial communities in the rhizosphere, eventually resulting in a positive plant-soil feedback (Bertin et al, 2003;Bais et al, 2006;Doornbos et al, 2012;De-la-Peña and Loyola-Vargas, 2014;Ma et al, 2017). Evidence is accumulating that certain beneficial microorganisms suppress plant-parasitic nematodes by inducing systemic resistance (ISR) in plants (Reitz et al, 2000;Munif et al, 2001;Siddiqui and Shaukat, 2004;Dababat and Sikora, 2007;Adam et al, 2014b;Selim et al, 2014;Martínez-Medina et al, 2017b;Elhady et al, 2018;Kang et al, 2018;Silva et al, 2018;. In the initial phase of microbially induced plant defense the pattern recognition receptors localized on the plant cell membranes recognize molecular structures on the microbe/ pathogen surface that are referred to as microbe/pathogenassociated molecular patterns (MAMP/PAMP) (Jones and Dangl, 2006).…”
Section: Introductionmentioning
confidence: 99%